Gender and Migration in Times of COVID-19: Additional Risks on Migrant Women in the MENA and How to Address Them - Lilian Diab, Jasmin (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Jasmin Lilian Diab Title (English): Gender and Migration in Times of COVID-19: Additional Risks on Migrant Women in the MENA and How to Address Them Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 162-164 Page Count: 3 Citation (English): Jasmin Lilian Diab, “Gender and Migration in Times of COVID-19: Additional Risks on Migrant Women in the MENA and How to Address Them,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 162-164.